Конституціоналізація стратегічного курсу України в контексті доктрини юридичної відповідальності держави - Бакумов, О. С.; Bakumov, O. S.; ORCID: http://orcid.org/0000-0002-4003-1974 (Право і безпека. – 2018. – № 4 (71). – С. 13-21, 2018)
Проблематику конституційного закріплення стратегічного курсу України проаналізовано через призму доктрини юридичної відповідальності держави. Наголошено, що ідея визнання цього курсу потребує своєї конституціоналізації, що сприятиме змістовному розгортанню та нормативній визначеності юридичної відповідальності держави як ключового елемента інституційного забезпечення правової держави, якою проголошено Україну. Обґрунтовано, що питання конституційно-проектних новацій у частині визначення стратегічного курсу України щодо набуття членства в ЄС і НАТО потребуватимуть посиленої уваги з боку парламенту України. За умови прийняття ідеї фіксації такого курсу в розділі І Конституції України відповідні зміни мають затверджуватися на всеукраїнському референдумі, що надасть конституціоналізації згаданого курсу найвищий рівень легітимності.

The article is focused on studying the problems of constitutional consolidation of the strategic course of Ukraine. It is analyzed through the prism of the doctrine of legal liability of the state. It has been concluded that the idea of admitting the strategic course of Ukrainian state needs the constitutionalization. This will contribute to the content development and normative absolutism of the legal liability of the state as a key element of the institutional provision of a lawgoverned state, as Ukraine is proclaimed to be. On the author’s opinion, the method of establishing such a course in the Constitution of Ukraine, suggested in the Draft Law No. 9037, through the consolidation of new powers for the supreme agencies of state power of a temporary nature in the basic Sections of the Constitution of Ukraine, can not be regarded as optimal, both from the conceptual and technically legal points of view. The author has substantiated that the issues of constitutional and law-making innovations in determining the strategic course of Ukraine for acquiring the membership in the EU and NATO will require increased attention from the Ukrainian parliament. In case of adopting the idea of establishing such a course, appropriate amendments to the Section I of the Constitution of Ukraine, should be approved at the All-Ukrainian referendum, which should add to the constitutionalization of the above-mentioned course of the highest level of legitimacy.

Проблематика конституционного закрепления стратегического курса Украины проанализирована через призму доктрины юридической ответственности государства. Утверждается, что идея признания данного курса нуждается в конституционализации, что будет способствовать содержательному развёртыванию и нормативной определённости юридической ответственности государства как ключевого элемента институционального обеспечения правового государства, которым провозглашена Украина. Обосновано, что вопросы конституционно-проектных новаций в части определения стратегического курса Украины на обретение членства в ЕС и НАТО будут требовать усиленного внимания со стороны парламента Украины. При условии принятия идеи фиксации такого курса в разделе I Конституции Украины соответствующие изменения должны утверждаться на всеукраинском референдуме, который придаст конституционализации упомянутого курса наивысший уровень легитимности.
Constitutionalization of the strategic course of Ukraine within the doctrine of legal liability of the state
Конституционализация стратегического курса Украины в контексте доктрины юридической ответственности государства
Бакумов, О. С. Конституціоналізація стратегічного курсу України в контексті доктрини юридичної відповідальності держави / Олександр Сергійович Бакумов // Право і безпека. – 2018. – № 4 (71). – С. 13-21. – DOI: https://doi.org/10.32631/pb.2018.4.01.
Bakumov, O. (2018) Конституціоналізація стратегічного курсу України в контексті доктрини юридичної відповідальності держави, Право і безпека, 71(4), pp 13-21. doi: 10.32631/pb.2018.4.01.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; стратегічний курс держави; європейська інтеграція; юридична відповідальність держави; внесення змін до Конституції України; конституційна реформа; strategic course of the state; integration towards Europe; legal liability of the state; amendments to the Constitution of Ukraine; constitutional reform; стратегический курс государства; европейская интеграция; юридическая ответственность государства; внесение изменений в Конституцию Украины; конституционная реформа